Optimal Pricing of Virtual Goods with Conspicuous Features in a Freemium Model. Issue 3 (3rd July 2019) - Geng, Wei; Chen, Zuguang
ABSTRACT: In a freemium business model, the pricing of virtual goods with conspicuous features is a key challenge, because firms face a trade-off between increasing the total installed base and maintaining scarcity. In this study, we establish a model to facilitate this trade-off by considering a reference-based utility shift related to conspicuous consumption, and we offer the optimal pricing strategy for a monopoly firm, given different levels of snobbery. In addition, we provide guidelines for the firm on the conditions of introducing a freemium model. Our results reveal that the firm earns a growing profit by ratcheting up the premium price as the intensity of snobbery increases beyond a certain threshold, and in mild configurations, the firm earns a higher profit if it increases value discrepancy between the free and premium versions. This study contributes to theories of pricing virtual goods and may help practitioners who sell virtual goods with conspicuous features.